2019
DOI: 10.1111/jfpp.14195
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of enzymatic browning in sweet potato (Ipomoea batatas(L.)) with chemical and natural anti‐browning agents

Abstract: Honey, pineapple, chilli pepper, and onion extracts were investigated for their ability to inhibit enzymatic browning in sweet potatoes. Honey had the highest inhibition (41.39%–48.0%), comparable with l‐ascorbic acid. Heated onion extract increased polyphenol oxidase (PPO) inhibition by 2.5‐fold when 4‐methylcatechol was used as substrate. However, percentage inhibition decreased drastically (7.42%–19.67%) when heated pineapple extract was used. Fresh chilli pepper extract showed a higher PPO inhibition (45.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 29 publications
(48 reference statements)
5
39
2
1
Order By: Relevance
“…IC 50 value for ascorbic acid in similar studies was found, 069 mM for tea leaf PPO (Öztürk et al, 2020), 0.80 mM in sweet potato PPO (Lim et al, 2019) (Han et al, 2019).…”
Section: The Effect Of Inhibitorsmentioning
confidence: 58%
“…IC 50 value for ascorbic acid in similar studies was found, 069 mM for tea leaf PPO (Öztürk et al, 2020), 0.80 mM in sweet potato PPO (Lim et al, 2019) (Han et al, 2019).…”
Section: The Effect Of Inhibitorsmentioning
confidence: 58%
“…Moreover, the Maillard pathway/route linked with the pH value in the range of pineapple juice (3.52-5.2) is associated with the formation of HMF via 1,2 enolization of ARPs at pH ≤ 7. We are, therefore, linking the results reported above by Rattanathanalerk et al (2005) concerning HMF formation and those by Lim et al (2019). However, properties.…”
Section: Pineapple (Ananas Comosus) Juice Extractssupporting
confidence: 76%
“…The superiority of heated over unheated/fresh plant extracts in inhibiting EB was attributed to the development of the MR during heating, thus production of MRPs (Barbagallo et al, 2012;Kim et al, 2005;Lim et al, 2019;Redondo et al, 2016;Wong & Angel Lee, 2014). Although authors concluded thus, only the study conducted by Redondo et al (2016) Abbreviations: L-DOPA, L-dihydroxy phenylalanine; PPO, polyphenoloxidase; REA, residual enzyme activity which is also termed relative enzyme activity.…”
Section: He Ated Pl Ant E X Tr Ac Ts a S Inhib Itor S Of Enz Ymati mentioning
confidence: 99%
See 1 more Smart Citation
“…(Okada, Katsura & Kobayashi, 2004;Purlis & Salvadori, 2007;Troup et al, 2015;Lee & Knag, 2017). However, browning can affect the flavor and reduce the nutritional value of most fruits and vegetables and is therefore considered the second largest cause of quality loss (Lim, Cheun & Wong, 2019). The two main types of browning are as follows: enzymatic browning, which is the result of polyphenol oxidase (PPO) that catalyzes the formation of quinone and its polymer; and non-enzymatic browning, which involves Maillard reaction and caramelization (Buera et al, 1987;Zamora & Hidalgo, 2005).…”
Section: Introductionmentioning
confidence: 99%